Globalization: the implication for Russia - Erokhin, Vasilii (Henry Stewart Talks, 2014)
Globalization: idea and contemporary approaches, Global challenges for economies in transition, Russia and alternative global powers (BRICS, China, EurAsEC), Russia as an initiator of geopolitical reshaping: winner or loser?, Russia under Western sanctions: expected course of events